Multiwalled carbon nanotube-dispersive solid-phase extraction followed by high performance capillary electrophoresis for simultaneous determination of six adulterants in antihypertensive functional foods. Issue 2 (26th November 2014) - Zeng, Li; Wu, Xin; Li, Yongxin; Lu, Dan; Sun, Chengjun
Abstract : A novel, simple and accurate high performance capillary electrophoresis method after multiwalled carbon nanotube-dispersive solid-phase extraction was developed for simultaneous determination of hydrochlorothiazide (HCT), chlortalidone (CTD), indapamide (IDP), reserpine (RSP), nifedipine (NDP) and valsartan (VST) in antihypertensive functional foods. Abstract : A novel, simple and accurate high performance capillary electrophoresis method after multiwalled carbon nanotube-dispersive solid-phase extraction was developed for simultaneous determination of hydrochlorothiazide (HCT), chlortalidone (CTD), indapamide (IDP), reserpine (RSP), nifedipine (NDP) and valsartan (VST) in antihypertensive functional foods. After the analytes were ultrasonically extracted with acetonitrile, they were adsorbed on multiwalled carbon nanotubes (MWCNTs). Then the MWCNTs were separated through centrifugation and the analytes on the MWCNTs were desorbed with methanol. The eluent was removed through rotary evaporation and the residue was dissolved in acetonitrile–water (50 : 50, v/v) for CE analysis. The electrophoresis separation was carried out on an uncoated fused-silica capillary (57.0 cm total length and 50.0 cm effective length, 75.0 μm i.d.) by applying a voltage of 30 kV and the running buffer consisting of 10 mM borax buffer, 20 mM SDS and 30% acetonitrile (pH 9.7) with PDA detection at 220 nm. The capillary column temperature was set at 30 °C. The method showed good linearity in the ranges of 1–50 μg mL −1 with LODs of 0.058–0.157 μg mL −1 . The proposed method was successfully applied to the analysis of antihypertensive functional foods with different matrices. Reserpine was detected in a sample with the content of 55.1 ± 0.9 μg mL −1 while other chemicals were not detected in all samples. The results of the proposed method were compared with those obtained by HPLC and there were no significant differences in the performance of the methods regarding accuracy and precision.